The synergistic interaction between dithiophosphate and frothers at the air-water and mineral-water interface - Pienaar, Dandré (Department of Chemical Engineering, 2022)
Collectors and frothers are reagents in the flotation process that are thought to have separate roles. Collectors selectively hydrophobized the mineral surface and frothers adsorb onto bubbles inhibiting bubble coalescence and stabilizing the froth. Interactions between these molecules have been previously reported in literature (Leja & Schulman, 1954; Lekki & Laskowski, 1971; Dai, Bradshaw & Harris, 2001; Jordaan, 2018). These interactions have been shown to improve sulphide mineral recovery. Dithiophosphate (DTP) is a collector in sulphide mineral flotation which has been shown to synergistically increase flotation recovery in the presence of frothers (Pienaar et al., 2018) but it has also been shown that DTP does not adsorb onto the sulphide mineral surface (Nagaraj & Brinen, 2001; McFadzean & O'Connor, 2014; Petrus et al., 2011; Grano et al., 1997; Guler et al., 2006; Taguta, O'Connor & McFadzean, 2017) as occurs with conventional collectors. If DTP does not adsorb onto the mineral surface and improve hydrophobicity it was not clear what the role of DTP is in the flotation process. The main objective of this research was to identify the role of DTP in sulphide mineral flotation. Each of the respective interfaces were investigated for the adsorption of dithiophosphate (DTP). The adsorption of DTP on galena, pyrite, chalcopyrite and chalcocite was measured by UV-Vis spectrophotometry and isothermal titration calorimetry. Adsorption tests in the presence of aeration were used to determine if DTP dynamically transferred from the air-water to the mineral-water interface. At the air-water interface a regular solution theory approach, critical coalescence experiments and foam stability tests were used to quantify the interactions between DTP and frothers and compare them to xanthate and frothers. Microflotation and induction time experiments were performed to determine the effect of the collectors, frothers and their mixtures on mineral recovery and bubble-particle attachment It was found that DTP in the presence of a non-ionic frother synergistically improved sulphide mineral recovery. This improvement was attributed to attractive molecular interactions which were found to occur between the collector and the frother at the air-water interface. The interaction facilitated the transfer of the frother between the air-water and mineral-water interface, which destabilised the film between the bubble and the particle, improving film thinning kinetics and synergistically enhanced mineral recovery. When DTP did not adsorb onto the mineral surface, the collector co-adsorbed with the frother at the air-water interface and transferred with the frother onto the mineral surface during bubble-particle collision.